Analysis to entity mobility models of wireless ad hoc networks - LIU Yan-tao1; AN Jian-ping2; LU Ji-hua2; LIU Heng2 (Tongxin xuebao)
Stationary speed distribution of random waypoint model,random direction model,and random walk model were analyzed by Palm calculus.The hypostasis of speed decay was proved to be the correlation between speed and dura-tion within any movement period.Stationary node distribution of random waypoint model and random direction model were discussed,respectively,by Palm calculus and geometric probability.It turned out that nodes in these two models tended to be non-uniform.Last,based on the central limit theorem,trace endpoints of random walk model in boundless regions was proved to be governed by normal distribution.As a result,random walk model based on time combines the strengths of entity mobility models on the performance of stationary speed distribution and node distribution,so it be-comes the most reasonable one.